2012
DOI: 10.1002/polb.23102
|View full text |Cite
|
Sign up to set email alerts
|

Incremental optimization in donor polymers for bulk heterojunction organic solar cells exhibiting high performance

Abstract: The power conversion efficiency of an organic solar cell has now exceeded the 10% mark, which is a significant improvement in the last decade. This has been made possible due to the development of low-band-gap polymers with tunable electron affinity, ionization potential, solubility, and miscibility with the fullerene acceptor, and the improved understanding of the factors affecting the critical device parameters such as the V OC and the J SC . This review examines the latest strategies, results, and trends th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 100 publications
(206 reference statements)
0
19
0
Order By: Relevance
“…The EA of TIB−Si is the largest, which indicates that the electron transfer capability of TIB−Si is strong, and it was more advantageous of electrons injection . Comprehensive comparison of the original and designed molecules can be found that TIB−Si molecule has a smaller IP (5.41 eV) and a larger EA (2.15 eV), and TIB−Si has better charge transfer capability …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EA of TIB−Si is the largest, which indicates that the electron transfer capability of TIB−Si is strong, and it was more advantageous of electrons injection . Comprehensive comparison of the original and designed molecules can be found that TIB−Si molecule has a smaller IP (5.41 eV) and a larger EA (2.15 eV), and TIB−Si has better charge transfer capability …”
Section: Resultsmentioning
confidence: 99%
“…[32] Comprehensive comparison of the original and designed molecules can be found that TIBÀSi molecule has a smaller IP (5.41 eV) and a larger EA (2.15 eV), and TIBÀSi has better charge transfer capability. [33]…”
Section: Ionization Potential and Electron Affinitymentioning
confidence: 99%
“…Some aspects of these isoindigo properties were briefly discussed in some reviews. [88][89][90][91][92] Synthetic applications of isoindigo are mainly based on the creation of polymeric structures. Variation of substituents both at the nitrogen atom and the side chain is directed towards improving the physical and chemical characteristics of the target compounds: solubility, UVvisible absorption, electron affinity and others.…”
Section: Isoindigo In Organic Solar Cell Productionmentioning
confidence: 99%
“…Fused aromatic and heteroaromatic ring containing compounds have by now gained significant attention due to their extensive applications in advanced electronic and optoelectronic devices . The 5,11‐dihydroindolo[3,2‐b] carbazoles (ICZs) have a ladder type planar structure similar to pentacenes .…”
Section: Introductionmentioning
confidence: 99%